2022
DOI: 10.5194/bg-2022-221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Process Rate Estimator: A novel model to predict total denitrification using natural abundance stable isotopes of N2O

Abstract: Abstract. Total denitrification, the natural process capable of removing reactive N from ecosystems through conversion to N2, is one of the most poorly constrained processes in terrestrial N cycling. In situ quantification of total denitrification could help identify mitigation options for N pollution. This study provides proof-of-concept for a novel natural abundance isotope based model for depth differentiated in situ quantification of total denitrification; it does so by examining the use-case of the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These isotope values are the net result of various production and consumption mechanisms, with isotope effects associated with these processes. It has been recently suggested that numerical solvers may be able to estimate gross rates of various processes if N 2 O and multiple isotopes are considered simultaneously, and an accurate understanding of the isotope effects of the processes is known (Decock et al., 2023). However, in that study, the method largely calculated larger N 2 O consumption rates than production rates (their Table 3), yet the soils had positive surface fluxes.…”
Section: Model Experiments and Comparison With Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These isotope values are the net result of various production and consumption mechanisms, with isotope effects associated with these processes. It has been recently suggested that numerical solvers may be able to estimate gross rates of various processes if N 2 O and multiple isotopes are considered simultaneously, and an accurate understanding of the isotope effects of the processes is known (Decock et al., 2023). However, in that study, the method largely calculated larger N 2 O consumption rates than production rates (their Table 3), yet the soils had positive surface fluxes.…”
Section: Model Experiments and Comparison With Observationsmentioning
confidence: 99%
“…As with isotopes in soil CO 2 , the depth profiles can only be interpreted through the lens of a physics‐based model (e.g., Cerling, 1984). There are a number of papers that have proposed, or used in a limited fashion, production‐diffusion models to examine soil N 2 O concentrations versus depth (e.g., Decock et al., 2023; Goldberg et al., 2008; Hosen et al., 2000; Rock et al., 2007; Shcherbak & Robertson, 2019; Verhoeven et al., 2018). Well and Flessa (2008) measured the effect of diffusion on the isotope composition, and concluded that diffusive isotope fractionation in non‐steady state conditions must be included in data interpretations.…”
Section: Introductionmentioning
confidence: 99%